Effect of printing parameters on material distribution in spray-based 3D concrete printing (S-3DCP) - Lu, Bing (2021)
The adoption of 3D concrete printing (3DCP) contributes to the increase of automation and efficiency in construction. Recently, spray-based 3D concrete printing (S-3DCP) has been proposed specifically for vertical and overhanging applications, such as facades and ceiling decorations. Nevertheless, it is still very premature due to limited research studies on how various printing parameters affect material distribution in S-3DCP. This study tackles the issue by focusing on the effect of printing parameters, i.e., pumping rate, air injection pressure, nozzle travel speed, and nozzle standoff distance. Firstly, an analytical model was constructed involving a two-stage deposition process, i.e., under-compaction and full-compaction stages. The transition from the first stage to the second one occurred when the predicted section mass reaches critical section mass. The widths and average thicknesses of the sprayed filament were calculated in both stages, and material distribution was described with trapezoid function. Afterwards, a series of single-layer spray experiments was conducted to analyze the effect of printing parameters on material distribution and determine the constants in the proposed analytical model. Finally, the analytical model was validated by multiple-layer spray experiments. The average relative errors in predicting widths and average thicknesses were 15.29% and 9.92%, respectively, which illustrate the effectiveness of the model. The proposed analytical model can help guide the selection of printing parameters for S-3DCP, i.e., choosing suitable printing parameters for desired filament width and thickness. Furthermore, it can be utilized in the feedback control of spray-based 3D printing systems for efficiency improvement. The S-3DCP enhanced by the model has the potential to revolutionize the construction of vertical and overhanging decorative structures, such as customization of profiles, defect repair, and quantitative deposition of functional coatings.